IMPLEMENTASI FILSAFAT PENDIDIKAN PADA SEKOLAH DASAR - Eka Fitriyani Achmad; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Cakrawala Ilmiah, 2022)
The philosophy of education is the product of deep thought and meditation upon education. Philosophy is the way out and education follows it and the problems of education can be answered using philosophy. The goal of research is to describe dsara's school knowledge with educational philosophy. The author compiled the data into a journal article. ranging from 2018 to 2022. Home-schooled results from the Google schoolar electronic database. May result in the importance of the implanting of a elementary school philosophy of education that becomes a formal school education that makes a child a guiding child in his or her stages of life.